2011
DOI: 10.1103/physreve.84.031704
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior and properties of the liquid-crystal dimer 1′′,7′′-bis(4-cyanobiphenyl-4′-yl) heptane: A twist-bend nematic liquid crystal

Abstract: The liquid-crystal dimer 1'',7''-bis(4-cyanobiphenyl-4'-yl)heptane (CB7CB) exhibits two liquid-crystalline mesophases on cooling from the isotropic phase. The high-temperature phase is nematic; the identification and characterization of the other liquid-crystal phase is reported in this paper. It is concluded that the low-temperature mesophase of CB7CB is a new type of uniaxial nematic phase having a nonuniform director distribution composed of twist-bend deformations. The techniques of small-angle x-ray scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
598
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 573 publications
(648 citation statements)
references
References 52 publications
47
598
2
1
Order By: Relevance
“…There had been a number of reports of nematic-nematic phase transitions for bent-core or banana mesogens, but the structural characteristics of the new nematic phases had not been identified. 1,[2][3][4][5][15][16][17] However, recently a very detailed investigation of the flexible bent-shaped liquid crystal dimer 1 00 ,7 00 -bis(4-cyanobiphenyl)-4 0 -yl heptane (CB7CB) 6 concluded that one of the two nematic phases exhibited by this compound is the twistbend nematic phase (N TB ), in agreement with Dozov's predictions. 13 The mesogen CB7CB now appears to be the model liquid crystal on which research about this new phase is mainly focused.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…There had been a number of reports of nematic-nematic phase transitions for bent-core or banana mesogens, but the structural characteristics of the new nematic phases had not been identified. 1,[2][3][4][5][15][16][17] However, recently a very detailed investigation of the flexible bent-shaped liquid crystal dimer 1 00 ,7 00 -bis(4-cyanobiphenyl)-4 0 -yl heptane (CB7CB) 6 concluded that one of the two nematic phases exhibited by this compound is the twistbend nematic phase (N TB ), in agreement with Dozov's predictions. 13 The mesogen CB7CB now appears to be the model liquid crystal on which research about this new phase is mainly focused.…”
Section: Introductionsupporting
confidence: 53%
“…However, it is known that pure CB7CB dimer exhibits a firstorder N TB -N phase transition. 6 The inset of Fig. 2 shows how the nematic range increases from pure CB7CB dimer when the concentration of CB7CB in the binary mixtures decreases, showing a behaviour analogous to binary mixtures exhibiting the smectic A (SmA) to nematic phase transition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations